Penerapan Strategi Multi Level Marketing Melia Sehat Sejahtera Pada Masa Pandemi Covid-19 Perspektif Ekonomi Syariah - Ayu Mufriyani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to determine the new strategy of PT. Melia Sehat Sejatera Mataram City during the COVID-19 pandemic and analyzed this strategy using a sharia economic perspective. This research uses qualitative methods, data collection techniques are carried out by combining and inductive data analysis. The results of this study stated that there were two new strategies implemented by Melia Sehat Sejahtera Mataram City during the covid-19 pandemic, namely the door to door strategy, sales and recruitment of prospective members through social media or online. The implementation of the Mult Level Marketing strategy of Melia Sehat Sejahtera Mataram City during the Covid-19 pandemic that was honest, transparent and fair is a marketing practice that has been exemplified by Rasulullah during his time as a trader. However, from a sharia economic perspective, the door to door strategy of the Melia Sehat Sejahtera Multi-Level Marketing business in Mataram City during the Covid-19 pandemic is not in accordance with the basic principles of sharia marketing.